PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARYAWAN TERHADAP PRODUKTIVITAS KERJA DENGAN MOTIVASI - Wulandari, Indri; Elfiswandi, Elfiswandi; Candana, Dori Mittra; Fitri, Elva Rahmi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The study aims examine the effec of Job training and employee development on work productivity, with motivation as an intervening variable, using primary data obtained by disseminating questionnaires to 60 employees as respondents at PT. United Tractors Tbk Cabang Padang. In this study, we used the Structural Equation Modeling (SEM) analysis tool using Partial Least Squares (PLS).The results of the research show that, There is a positive and significant influence between Job Training on Motivation at PT. United Tractor, There is a positive and non-significant influence between Employee Development at Motivation at PT. United Tractor, There is a positive and significant influence between Job Training at Employee Productivity at PT. United Tractor, There is a positive and significant influence between Employee Development at Work Productivity at PT. United Tractor, There is a positive and non-significant influence between Motivation on Work Productivity at PT. United Tractor, There is a positive and non-significant effect of Job Training on Work Productivity through Motivation at PT. United Tractor and There is a positive and non-significant influence between Employee Development on Work Productivity through Motivation at United Tractors.